Mechanism of Apoptosis Induction in Oral Cancer Cells by Uncaria-derived Flavonoids - Ridho, Fiki Muhammad; Iqbal, Mohammad; Agustina, Arista Widya; Syachputra, Andika Julyanto (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2023)
Introduction: Oral cancer is cancer that occurs in the oral cavity and oropharynx, ranking 16th as the most common cancer found with a number of new cases of 377,713 and a number of deaths of 177,757 cases in 2020. Several types of flavonoids contained in the genus Uncaria were found to have anticancer bioactivity, one of which is inducing apoptosis in oral cancer cells. Aim: This study aims to review the potential and mechanisms involved of flavonoids in inducing apoptosis in oral cancer cells. The literature review method was used in this study by conducting a systematic literature search on PubMed, ScienceDirect, and Google Scholar until October 2023. Results: A total of 13 studies were included in this study and our findings conclude that flavonoids, especially quercetin, kaempferol, rutin, umbelliferon, and epigallocatechin gallate (EGCG), have the potential to be used as anticancer agents, one of which has the ability to induce apoptosis, both through extrinsic and intrinsic pathway, in several oral cancer cell lines, including SCC-4, SCC-9, SCC-25, SAS, KB/VCR, Tca-8113, YD10B, YD38, MC-3, KB, and HSC-3, through the mechanism of inhibiting anti-apoptotic expression, activating pro-apoptotic protein expression, generating ROS, and regulating PI3K/AKT, MAPK, and JAK/STAT signaling pathways. Conclusion: We conclude that Uncaria-derived flavonoids hav the potential to induce apoptosis, both extrinsic and intrinsic, in oral cancer cells.